Serverless Computing: Cloud Run and App Engine Analysis in Profile Website Deployment - Maulidia, Zirlyfera Zakiya; Venica, Liptia (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Cloud Computing enables individuals or companies to obtain network access on-demand, including servers, storage, and applications. Google, as one of the Cloud Computing service providers, offers Google Cloud Platform (GCP) with various computing services. Two serverless computing options Google provides for server management are Cloud Run and App Engine. Although both services share similarities in server management and infrastructure, it is essential to analyze their differences to gain a better understanding of serverless computing on the Google Cloud Platform. This study utilizes a qualitative method for gathering information and follows the Extreme Programming method for website development. This approach shows that users need not be concerned about servers or infrastructure management as Google takes care of it entirely. Four things are different in Cloud Run and App Engine: definition, features, deployment process, and usability.